Clinical profile and comparison of causality assessment tools in cutaneous adverse drug reactions - Ranjana Beniwal; Lalit Kumar Gupta; Ashok Kumar Khare; Asit Mittal; Sharad Mehta; Manisha Balai (Wolters Kluwer Medknow Publications, 2019)
Background: Cutaneous adverse drug reactions (CADRs) are probably the most frequent of all manifestations of drug sensitivity. As a considerable number of new drugs are periodically introduced into the market, the incidence of CADR is likely to increase. The pattern of CADR and the causative drugs is likely to change accordingly. There is no uniformly accepted and reliable method of objectively assessing the causal link between drug and adverse reaction. Aim: To study the clinical patterns and causative drugs and compare causality assessment [World Health Organization (WHO) and Naranjo algorithm] of CADR among patients attending the dermatology department. Materials and Methods: This is a cross-sectional hospital-based study in which all patients with suspected CADR attending the dermatology department of a tertiary care center over a 9-month period were evaluated using the causality assessment criteria recommended by the WHO-Uppsala Monitoring Centre (UMC) and Naranjo scale. The severity of the reaction was assessed using Adverse Drug Reaction Severity Assessment Scale (modified Hartwig and Siegel scale). Results: A total of 200 consecutive patients with CADR were evaluated. The causality assessment for a drug as per WHO scale yielded 63 (31.5%) cases as certain, 12 (6%) as probable, and 125 (62.5%) as possible, whereas Naranjo scale showed 26 (13%) cases to be definite, 138 (69%) as probable, and 36 (18%) as possible. There was poor agreement between the two scales. Fixed drug eruption was the most common pattern of CADR (82.41%). The average number of drugs received by patients was 2.09. The most common suspected drug group was antimicrobials (n = 170; 40.5%), followed by nonsteroidal anti-inflammatory drugs (n = 148; 35.3%) and antiretroviral drugs (n = 41; 9.7%). Fixed drug eruption was most commonly caused by paracetamol. Antiepileptics and antimicrobials were the most common suspects among severe cutaneous adverse reactions. Limitations: Multiple concomitant drug usage by patients and inability to provoke all patients/measure drug levels in blood resulted in higher number of drugs with causal association as probable/possible. Conclusion: WHO-UMC scale was found to be easier to apply and evaluate, with greater practical utility. Poor agreement between the two commonly used scales emphasizes the need for a consistent and uniform causality assessment tool.